A MESSAGE FROM THE AMERICAN SOCIETY. - Harrison, W. L. (The Accounting Review, 1926)
Abstract The article discusses on a speech delivered by the secretary of American Society of Certified Public Accountants W.L. Harrison. Those primarily interested in accounting felt that when the law was originally passed that experience was the primary method by which a man fitted himself to practice public accountancy. They established the requirement of five years' practice and only a high school education; flat same restriction is imposed today. A true profession it will be necessary for accountants to develop somehow a scheme of instruction that will eliminate to a large extent the necessity for practical experience upon the part of those who seek entrance into the profession. This Association is hiding its light under a bushel by not telling the rank and file of practitioners what one can do in the way of training a young man for entrance Into public accountancy. It depends upon the kind of education provided by this Association in educating the rank and file of C. P. As away from the idea, which prevails in the minds of, so many of them that accountancy is still something that must be learned, like bricklaying, by doing it. A revelation is going on sometimes rather strongly against the thought that the young man who has obtained his C. P. A. is entitled to a journeyman's wage. That false impression is to have thrown around the issuing of the certificate. Such is not the impression attaching to admission to the bar or the issue of the license to practice medicine